Enrichment of unsaturated fatty acids from palm oil by means of solubility difference / Noor Azmira Mohd Alwi - Mohd Alwi, Noor Azmira (2019)
Palm oil undergo saponification process with ethanolic sodium hydroxide to break the triglycerides into free fatty acids (FFA) and glycerol. Then, the FFA was crystallize with methanol by using methanol crystallisation method based on one parameter which is solubility difference. The crystallisation of FFA with methanol (w/w) varies in ratio starting from 0.5:10 (g/g), 1.0:10 (g/g), 1.5:10(g/g), 2.0:10 (g/g) and 2.5:10 (g/g). The mixture was crystallise in refrigerator with temperature -5ºC until -8ºC. After that, the mixture was separated using Buchner funnel in reduced pressure. The solution part was collected and dried in fume hood before undergo methylation technique. FFA was converted into FAME by methylation and analyse with GC-MS to obtain percentage of fatty acid. Based on the ratio, the optimum condition for FFA to soluble in methanol was 1.5:10 (g/g). The major unsaturated fatty acid that contain in palm oil were oleic acid and linoleic with percentage of 61.71% and 15.79% respectively. Besides that, the minor amount of saturated fatty acids also observed with percentage 20.77% for palmitic acid and 1.73% for stearic acid.